A case of polymyositis with breast cancer and gastric cancer - YAMAMOTO, Mitsugu; TAKAHASHI, Norihiko; TAKAHASHI, Hiromasa; HOSODA, Mitsuchika; TAGUCHI, Kazunori; HONMA, Shigenori (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
Polymyositis is associated with cancer at the rate of 3-15 percent. There were some reports about palliation of the symptoms after resection of the cancer, but the relation of cause and effect has never yet been revealed. A 61-year-old woman felt listless and had difficulty in breathing. She was diagnosed as polymyositis with high CK level and muscle biopsy. Detailed examination was performed, and detected a right breast cancer and an early gastric cancer. After steroid pulse therapy, we performed breast conserving surgery with axillary lymph node dissection and laparoscopy assisted distal gastrectomy. Postoperative course was fine. CK decreased to normal level, and muscle strength recovered. Polymyositis has not relapsed and steroid dosage is tapering off.